The affective turn: an embodied view of the migrant experience (Andamios, Revista de Investigación Social, 2026)
This article aims to discuss how the affective turn allows us to reconfigure our understanding of the migratory phenomenon. Based on the systematization of two research experiences conducted with migrants during their passage through Chiapas, it is argued that emotionality, pain, corporeality, and affect are essential dimensions for understanding human mobility. Using ethnographic and collaborative methodologies, and from a horizontal accompaniment approach, oral and graphic testimonies are made visible as forms of enunciation that denounce structural violence and open possibilities for symbolic and emotional agency. The conclusion is that emotions and bodies, far from being residual or anecdotal, emerge as spaces for knowledge production in contexts of international migration.
Keywords: Affective turn; corporality; migration; emotions; collaborative ethnography